ChemInform Abstract: Synthesis, Crystal Structure, and Magnetic Properties of the Oxometallates KBaMnO4 and KBaAsO4. Issue 49 (9th December 2014) - zur Loye, Karl D.; Chance, W. Michael; Yeon, Jeongho; zur Loye, Hans‐Conrad
Abstract Single crystals of the new compound KBaAsO4 are prepared from a mixture of As2O3, Ba(NO3)2, KOH, and H2O (autoclave, 230 °C, 24 h) and single crystals of KBaMnO4 are obtained from a mixture of Ba(OH)2, KMnO4, KOH, NaOH, and H2O (autoclave, 230 °C, 12 h).